Official methods and recommended practices of the AOCS
Since the 1920s, the global fats and oils industry has relied on the analytical integrity of the Official Methods and Recommended Practices of the AOCS. The AOCS has set the standard for analytical methods critical to processing, trading, utilizing, and evaluating fats, oils, and lipid products. Worldwide acceptance has made the AOCS Methods a requirement wherever fats and oils are analyzed. The Official Methods and Recommended Practices of the AOCS contains currently recognized methodology required for proficiency testing in the Laboratory Proficiency Program (LPP), as well as AOCS Laboratory Certification. Additionally, AOCS methods are internationally recognized for trade, and several are listed by the Codex Alimentarius Commission. . . Item Details: Offered in several different formats, the Official Methods and Recommended Practices of the AOCS, 6th Edition, 3rd printing is an essential tool for ensuring analytical integrity. Comprehensive and Compatible. Each method has been reviewed and revised by academic, corporate, and government experts to ensure that the most technically advanced methods are presented. Reviewers have harmonized the methods with other well regarded scientific organizations such as AOAC International, IUPAC, AACC International, FOSFA International, IOC, and ISO.